Unusual Late Onset of Parenchymal Neuro-Behçet Disease - Wai Wai Miller; Demetrios Konstas; Chetan Gandhy; Derrick Robertson (Case Reports in Neurological Medicine)
Neuro-Behçet disease (NBD) is a multisystem inflammatory disorder characterized by oral lesions, genital lesions, uveitis, and neurological deficits. If left untreated, it may lead to worsening neurological function and can be fatal. Here we present a case of a 52-year-old woman who was diagnosed with Behçet disease (BD) as a teenager and had a relatively mild disease course. Decades later after her initial DB diagnosis, she presented to our hospital with a chief complaint of headache. She did not have focal neurological deficits or any active mucosal lesions. Upon further investigation, the patient was found to have multiple inflammatory changes on neuroimaging and abnormal cerebrospinal fluid (CSF), consistent with the diagnosis of NBD. She was treated with intravenous corticosteroid therapy and her symptoms resolved. Although our patient presented with minimal symptoms decades after her initial diagnosis, any neurological complaint warranted a thorough investigation for a proper diagnosis and treatment given the multisystem involvement of BD.